2021
DOI: 10.3389/fpsyg.2021.616637
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Online Wellbeing: A Scoping Review of Subjective Wellbeing Measures

Abstract: With the increasing importance of the internet to our everyday lives, questions are rightly being asked about how its' use affects our wellbeing. It is important to be able to effectively measure the effects of the online context, as it allows us to assess the impact of specific online contexts on wellbeing that may not apply to offline wellbeing. This paper describes a scoping review of English language, peer-reviewed articles published in MEDLINE, EMBASE, and PsychInfo between 1st January 2015 and 31st Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Although several humans–computer interaction studies underline the link between stress and individual well-being ( Garcia-Ceja et al, 2016 ), and ways that digital technologies can affect mental processes ( Passey, 2021 ), it is worth accentuating that there could be wider consequences in implementing digital technologies in the teaching settings. This might result in an interference with different indicators of well-being due to the complicated nature in the relationship between internet usage and subjective well-being ( Ong et al, 2021 ). In addition, research has indicated that cultural context plays a major role in subjective well-being ( Diener et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several humans–computer interaction studies underline the link between stress and individual well-being ( Garcia-Ceja et al, 2016 ), and ways that digital technologies can affect mental processes ( Passey, 2021 ), it is worth accentuating that there could be wider consequences in implementing digital technologies in the teaching settings. This might result in an interference with different indicators of well-being due to the complicated nature in the relationship between internet usage and subjective well-being ( Ong et al, 2021 ). In addition, research has indicated that cultural context plays a major role in subjective well-being ( Diener et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of similar work looking at the relationship between social-media language and positive aspects of psychology, such as resilience, life enrichment, and well-being, although there are notable exceptions (e.g., L. Mitchell et al's, 2013, work on happiness). This dearth is due, at least in part, to the fact that although there are some scales relevant to positive psychology and well-being (e.g., Angel et al, 2020;Swarbrick, 2006), they do not have the same ubiquity and acceptance as clinical measures of dysfunction (Ong et al, 2021). Consequently, there have been fewer data sets available for training algorithms that can link signals in digital life data to positive aspects of well-being.…”
Section: Language As a Lensmentioning
confidence: 99%
“…Measuring wellbeing has been a central task for the new science of wellbeing (Diener et al 2018). Wellbeing has been assessed and indexed using objective measures (e.g., physiological data, life expectancy as for country-level wellbeing) and subjective measures (e.g., self-reported happiness, life satisfaction; for reviews, see Conceição and Bandura 2008;Ong et al 2021). Though objective measures can provide some information on wellbeing, the majority of wellbeing assessments are subjective measures as wellbeing is largely idiographic (i.e., relating to an individual's own experiences and interpretations; Rose et al 2017;VanderWeele et al 2020).…”
Section: The Assessments Of Wellbeingmentioning
confidence: 99%
“…In addition, much wellbeing information is collected only once per year, limiting the assessments' ecological validity. One recent review (Ong et al 2021) indicated that only 1.7% assessments ask for the reporting of wellbeing at the momentary level. As hedonic wellbeing (e.g., positive or negative emotions) is highly sensitive to situations, wellbeing assessments with high ecological features are imperatively needed.…”
Section: The Assessments Of Wellbeingmentioning
confidence: 99%